Perbandingan Hasil Kadar Bilirubin Total pada Serum Segera dan Penundaan Selama 24 Jam dengan Suhu 20-25°C menggunakan Metode End-point - Historiani Akhmad, Sela; Anwar, Chairil; Widyantara, Aji (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
the biliary system. The stability of bilirubin levels in serum is greatly influenced by storage conditions, particularly the duration and temperature. Prolonged storage of serum at room temperature can cause a decrease in bilirubin concentration, thereby affecting the accuracy of the test results. This study aims to compare the total bilirubin levels in serum analyzed immediately with serum subjected to a 24-hour delay at a temperature of 20–25°C, using the End-point method. This research is an analytical observational study employing an experimental design with a cross-sectional approach. Data were collected through purposive sampling by distributing questionnaires to 18 staff members in PKU Muhammadiyah Hospital Wonosobo. Data analysis began with the Shapiro-Wilk normality test, followed by the Paired Sample t-Test. The results showed a statistically significant difference in total bilirubin levels between the immediately analyzed serum (mean = 0.52 mg/dL) and the serum delayed for 24 hours (mean = 0.22 mg/dL). The significance value (2-tailed) of 0.001 indicates that p < 0.05; thus, the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. The decrease in bilirubin levels after storage for 24 hours reached approximately 59%. These findings indicate that storing serum with a 24-hour delay at room temperature (20–25°C) without light protection can significantly reduce total bilirubin levels. Therefore, it is recommended that the examination be conducted immediately or the serum be stored in dark conditions, such as wrapped in aluminum foil, to maintain the stability of the bilirubin levels.